A comparative study on various indicators for evaluating soil health of three biochar materials application. (1st April 2022) - Wang, Gehui; Liu, Fang; Tariq, Muhammad; Wan, Jiang; Liang, Weiyu; Zhang, Wei; Peng, Cheng; Yang, Jie
Abstract: The application of biochar materials in metal(loid)s-polluted soil has been widely explored, while lesser is known about their potential threats to ecological environment. The impacts of biochar, Fe3 O4 supported biochar, and sulfide Fe3 O4 supported biochar both in the clean and arsenic (As)/lead (Pb) contaminated soil were systematically investigated by laboratory simulation experiments. Results showed that two of them, biochar and Fe3 O4 supported biochar revealed a positive role in improving soil fertility, promoting soil enzyme activities, and maintaining microbial community stability, while these positive effects were observed less by sulfide Fe3 O4 supported biochar due to its special morphology, amorphous structure, surface characteristics, and more Fe release. In the contaminated soil, the bioavailability of As/Pb were significantly reduced after using these materials, which further decreased the accumulation of As and Pb in earthworms alleviating their oxidative damage. Moreover, the addition of modified biochars could promote the richness of microbial community, but further inhibited the soil enzyme activities showing joint toxicity of biochar materials and co-existing of As and Pb metal(loid)s. We believe that our systematic approach and concluding findings will open a new window for a deeper understanding of ecological risks of biochar materials and application potential in soils. Graphical abstract: Image 1 Highlights: The trend of toxicity parameters was observed as BC < Fe-BC < S/Fe-BC. More adverse impacts of S/Fe-BC were attributed to its incomplete lattice structure and chemical properties. Biochar added in clean soil improved microbial activities, while inhibited E. fetida performance. Modified biochar reduced As/Pb contents in E. fetida and facilitated bacterial richness.